PENYUSUNAN ANGGARAN PENJUALAN DAN PENGARUHNYA TERHADAP PERENCANAAN PRODUKSI - Anggun Rohaya Putri Munthe; Mella Afrina; Nidaul Husna; Dini Vientiany (CV. Denasya Smart Publisher, 2026)
The sales budget is a crucial element in corporate planning because it serves as the primary basis for production planning. This study aims to analyze the preparation of the sales budget and its influence on production planning. The research employs a descriptive qualitative approach through a literature review of relevant academic books and journals. Data analysis is conducted by examining the conceptual relationship between the sales budget and production planning. The findings indicate that a systematically and realistically prepared sales budget enhances the effectiveness of production planning. The accuracy of the sales budget plays an important role in determining production volume in accordance with market demand, thereby minimizing the risk of overproduction or underproduction. In addition, interdepartmental involvement in the preparation of the sales budget supports more efficient production planning. Therefore, an effective sales budget has a strategic role in ensuring smooth production activities and achieving corporate objectives.